The Vatican in the family of nations diplomatic actions of the Holy See at the UN and other international organizations in Geneva - Tomasi, Silvano M. 1940- (Cambridge University Press, 2017)
"Based on a collection of statements delivered between 2003 and 2015, The Vatican in the Family of Nations provides a new understanding of the social doctrine and actions of the Catholic Church in international law and relations. These statements address contemporary issues which stir deep emotional responses, from disarmament and migrations, to discrimination and freedom of conscience. This volume disputes irrational fears of newcomers, offers reasonable adaptations to allow for peaceful coexistence, and insists on investigating the root causes of today's conflicts and displacements. As an independent voice, the Holy See offers these reflections with the view of prioritizing the common good before confessional interests, even when their aims and ends converge. In this sense, this book is a unique collection in international literature on the intersection of theology, human rights and social issues, which opens courageous new paths for the future"...